Abordagem da UEP em uma empresa de extração mineral: um estudo de caso - Moscatello, Newton (2015)
This research studied the behavior of production of a mineral extraction company, comparing the absorption costing method and the method of funding through the use of the UEP-stress production Unit to verify that this method showed a generation of more detailed data and information management to the administration. To this end, we used the model script troubleshooting Business Project (Business Problem Solving) of AKEN; Berends (2012) and VANDENBOSCH (2003). We used the data of the expenses incurred to calculate the costing method of the UEP-production Effort unit. The results, as the calculation of the unit cost of production per tonne, pointed to a similarity of monetary value, however it was found that among the methods analyzed, the costing method of the UEP-production Effort Unit presented more detailed cost management information with regard to the production process and with higher quality for analysis, allowing a enabling a more analytical knowledge of manufacturing capacity and the possible idleness. Its simplicity of use and ease of adoption of this method becomes attractive.